Marketing Communication Strategy Through Social Media To Increase Children Book Sales - Marina Wardaya (The Winners, 2016)
The purpose of this research was to determine the marketing communication strategy of children's books through social media in increasing sales. Qualitative research methods with the interpretive paradigm and the phenomenological approach were used in this research. The focus of this research was to observe about the children's books marketing communication strategy using social media, for instance with Facebook and Twitter to attract consumer’s interest in order to increase children's books sales. The results of this study show that the children's book marketing communication strategies in publisher’s social media are fully and interactively utilized, as seen from the various activities posted on Facebook and Twitter. As well as the positive response from consumers who show their interest and desire to buy books offered or follow the event being held in order to increase sales.